2016
DOI: 10.4103/0971-5916.178596
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of activity of hypothalamo-pituitary-gonadal axis in postmenopausal women suffering from severe acute illness

Abstract: Background & objectives:Postmenopausal women constitute an ideal model for studying the extent of hypothalamo-pituitary gonadal (HPG) axis suppression in critical illness as the gonadotropins are normally high and non-cyclical in them. The objective was to assess the impact of acute severe illness in postmenopausal women on the HPG axis and the activities of the hypothalamo-pituitary-adrenal (HPA), the hypothalamo- pituitary-thyroid (HPT) axes; and levels of serum prolactin, by comparison between critically il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Details of the study population and methodology have been reported elsewhere. [ 10 ] Briefly, 35 postmenopausal women (>60 years of age) admitted to the intensive care units (of Departments of Medicine and Neurology) with a variety of acute severe medical illnesses and having a Simplified Acute Physiology Score II (SAPS II)[ 11 ] >30 (consistent with an in-hospital mortality rate ≥10%) were recruited for the study. Predicted death rates for in-hospital mortality were calculated from the SAPS II based on the published formula.…”
Section: Ethodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Details of the study population and methodology have been reported elsewhere. [ 10 ] Briefly, 35 postmenopausal women (>60 years of age) admitted to the intensive care units (of Departments of Medicine and Neurology) with a variety of acute severe medical illnesses and having a Simplified Acute Physiology Score II (SAPS II)[ 11 ] >30 (consistent with an in-hospital mortality rate ≥10%) were recruited for the study. Predicted death rates for in-hospital mortality were calculated from the SAPS II based on the published formula.…”
Section: Ethodsmentioning
confidence: 99%
“…Sample size for the original study[ 10 ] was calculated for an expected 25% or greater reduction in mean gonadotropin levels in sick postmenopausal women when compared to healthy postmenopausal controls for a power of ≥80% and a significance level ( P < 0.05). The obtained minimum sample size was 27 for detecting change in LH and 29 for change in FSH.…”
Section: Ethodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hippocampal dentate gyrus is a region that is very sensitive to changes in the brain caused by estrogen. It is useful for studying the mechanisms of neurogenesis caused by a variety of factors involved in hypothalamic-pituitary-adrenal (HPA) axis adjustment (Agca, Batailler, Tillet, Chemineau, & Duittoz, 2008;Burgess & Handa, 1993;Li et al, 2011;Raj et al, 2016;Sheng et al, 2003;Zhang et al, 2016;Zhao et al, 2015). In other words, the glucocorticoid receptor (GR) is known as a main marker describing the regulatory mechanism of HPA axis and will be used a basis for determining the change in HPA axis regulation by estrogen deficiency in the present study.…”
Section: Introductionmentioning
confidence: 99%